Pengaruh Kinerja Lingkungan, Umur Perusahaan dan Proporsi Dewan Komisaris Independen pada Pengungkapan Informasi Lingkungan - Pawitradewi, Anak Agung Istri; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2020)
This study aims to determine the effect of environmental performance, company age and the proportion of independent commissioners on disclosure of environmental information. Samples from this study were 24 companies where this sample was obtained using a purposive sampling method with the criteria of high profile companies listed on the IDX and registered as participants in the 2016-2018 PROPER. Research data processing was performed using multiple linear regression data analysis techniques. The results obtained after testing are environmental performance and the proportion of independent commissioners has a positive influence on the disclosure of environmental information. While the results of the study found from the relationship between the age of the company on the disclosure of environmental information is found no influence between the two variables. Keywords: Environmental Performance; Company Age; Proportioni of Independent Commissioners; Environmental Disclosure.